Investigating critical success factors in online learning environments in higher education systems in the Caribbean*. Issue 3 (3rd July 2018) - Barclay, Corlane; Donalds, Charlette; Osei-Bryson, Kweku-Muata
ABSTRACT: Online learning has grown as a key method in education management over the last couple of decades. Studies have shown that significant investments in this technology are being made by universities, yet the full benefits expected have not been realized due to issues and challenges experienced by stakeholders such as learners and instructors in adopting and effectively using e-learning. This is especially true in developing economies where they may be attempting online delivery modes for the first time. In this study, we explore the question "What are the factors that influence university students' adoption and use of an e-learning system in the context of the English-speaking Caribbean?" using an extended technology acceptance model framework. Partial least squares analysis was used to test the derived research model and found that critical success factors influencing students' perception and use in online learning settings, particularly those within a developing economy conditions, include supportive cultural practices, access to computers, system or online environment availability, computer and online learning self-efficacy, user perception of usefulness and ease of use. These results have significant implications for university executives and policy-makers as they consider adopting online learning delivery modalities for users.